Richard Walsh (ed.), T&T Clark Companion to the Bible and Film. (2nd May 2019) - Kozlovic, Anton
Abstract : Richard Walsh (ed.), T&T Clark Companion to the Bible and Film. London: T&T Clark, 2018, pp. xii + 416, ISBN: 978-0-5676-6620-8 (hbk).